El genero Ficus L. (Moraceae) en Mexico - Ibarra Manriquez, G.=700 1 Cornejo Tenorio, G.; Gonzalez Castañeda, L.; Piedra Malagon, E.M.; Luna, A.
(Es, En)
Ilus., 73 ref.
Keywords: FICUS; MORACEAE; TAXONOMIA; COMPOSICION BOTANICA; DISTRIBUCION GEOGRAFICA; BIOGEOGRAFIA; ORGANISMOS INDIGENAS; MEXICO; PHARMACOSYCEA; UROSTIGMA; HIGO